The Ferriferous quadrilateral of Minas Gerais: an analysis of its productive structure in the period 2010 to 2019 (Gestão & Regionalidade, 2024)
The objective of this paper is to analyze the behavior of variable employment for selected sectors within the production structure of municipalities belonging to the Quadrilátero Ferrífero (QF) region - Minas Gerais. These sectors are linked to Technologies of Information and Communication, Smarts Cities and Activities that Characterize Tourism (ACTs). A specific aim of this study is to capture possible changes in the set, between the years 2010 and 2019, which benefit the productive diversification of this region. For this, the following regional economy techniques will be used: differential-structural method (shift-share); coefficients of specialization and localization. The main results show little or no regional advantage and / or specialization for sectors linked to TICs, except for the Education sector.
Keywords: Ferriferous Quadrilateral; Shift-share; Location and expertise